2021
DOI: 10.1016/j.idcr.2021.e01107
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated herpes simplex virus 2 as a complication of pregnancy

Abstract: Disseminated herpes simplex virus 2 (HSV-2) infection, is a rare but devastating infection in pregnancy women. We present the case of a 30-year-old gravida 3, para 2−0-0−2, at 26 weeks 2 days gestation who presented with eleven days of vague and indolent symptoms before a diagnosis of disseminated HSV-2 infection with associated hepatitis was made. While the patient clinically improved with empiric acyclovir treatment, possibility of significant harm to the fetus remained, and the patient request elective term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Additionally, previous studies have emphasized the signi cance of conducting diagnostic tests, such as polymerase chain reaction and viral culture, to con rm the presence of herpes simplex virus type 2 infection in the amniotic uid and fetal tissues [12]. These diagnostic tests are essential in con rming the vertical transmission of the virus and guiding appropriate management strategies, including antiviral prophylaxis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have emphasized the signi cance of conducting diagnostic tests, such as polymerase chain reaction and viral culture, to con rm the presence of herpes simplex virus type 2 infection in the amniotic uid and fetal tissues [12]. These diagnostic tests are essential in con rming the vertical transmission of the virus and guiding appropriate management strategies, including antiviral prophylaxis during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, a thrombus may also be observed as a response to inflammation [45]. It has been reported that transplacental or ascending HSV infection may induce CCV [28,41,55].…”
Section: Figure 2: Representative Sample Of Deciduitis the Infiltrati...mentioning
confidence: 99%